2013
DOI: 10.1007/s00280-013-2184-z
|View full text |Cite
|
Sign up to set email alerts
|

PD173074, a selective FGFR inhibitor, reverses ABCB1-mediated drug resistance in cancer cells

Abstract: Here, we report for the first time, PD173074, an inhibitor of the FGFR, to selectively reverse ABCB1 transporter-mediated MDR by directly blocking the efflux function of the transporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 43 publications
4
32
1
Order By: Relevance
“…However, knowledge of the impact of ABC transporters on resistance against FGFR TKIs is limited. So far, only reversal of ABCB1-mediated MDR by the pan-FGFR/VEGFR inhibitor PD173074 and, in agreement with our here presented data, also nintedanib has been described [33, 34]. In the current study we demonstrate that high level expression of ABCB1 is underlying acquired nintedanib resistance of the FGFR1-driven SCLC cell line DMS114 but not of the two NSCLC cell lines NCI-H1703 and NCI-H520.…”
Section: Discussionsupporting
confidence: 90%
“…However, knowledge of the impact of ABC transporters on resistance against FGFR TKIs is limited. So far, only reversal of ABCB1-mediated MDR by the pan-FGFR/VEGFR inhibitor PD173074 and, in agreement with our here presented data, also nintedanib has been described [33, 34]. In the current study we demonstrate that high level expression of ABCB1 is underlying acquired nintedanib resistance of the FGFR1-driven SCLC cell line DMS114 but not of the two NSCLC cell lines NCI-H1703 and NCI-H520.…”
Section: Discussionsupporting
confidence: 90%
“…16 In vivo and in vitro studies suggested that PD173074 inhibited FGF-induced neoangiogenesis and tumor growth while being exempt of general toxicity. [14][15][16][17] In this study, we found intraperitoneal injection of 20 mg/kg PD173074 decreased pulmonary arterial pressure and alleviated pulmonary vascular remolding. This was consistent with the previous studies that FGFR inhibition with SU5402 or dovitinib reversed pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 90%
“…13 PD173074 could block the proliferation and clonogenic growth as well as induce cancer cell-cycle arrest and apoptosis in a variety of cancer cell lines. [14][15][16] When used in vivo, this compound was shown to inhibit FGF-driven angiogenesis and tumor growth with no apparent general toxicity. 17 Therefore, it is regarded as a promising compound for in vivo inhibition of FGF signaling.…”
Section: Introductionmentioning
confidence: 98%
“…A number of chemosensitizers inhibiting eukaryotic ABC transporters and overcoming drug resistance in cancer cells were in clinical development (24,25). Although sensitizers that inhibit bacterial RND pump-mediated efflux so far have not been available for clinical use, such compounds have been described and include 1-(1-naphthylmethyl)-piperazine (NMP) and phenylalanine-arginine-␤-naphthylamide (PA␤N).…”
mentioning
confidence: 99%